Perception of masculinity in rural family structure - Özpulat, Funda (Journal of Human Sciences, 2021)
Research Problem/aim: The objective of this study is to determine the perception of masculinity in rural family structure Methods: This research is a descriptive and analytical study. The universe of the research, which was conducted between the dates of 14.11.2016 - 31.05.2017, is the people of Akşehir district of Konya Province. Individuals aged 18 and over (n=500), who participated voluntarily, were included in the research, particular attention was paid to acquire the written and verbal consents of the participants prior to the application. Findings: Participants are between the ages of 18 to 65 and the median age is 27.57±10.22. Almost all of the women, at 92.9%, disagree with the "the man should decide how to use the household income" statement, while 38,7% of men support this statement, it can be seen that the provided responses change according to genders (p=.000). Both genders accept the "the man is the head of the household" statement, while 39.5% of women agree with this statement, at high rates, at 74.9%, men support this statement. While both genders think it is the man's duty to provide for the family, the support rate for this statement among male participants is significantly higher, at 71.2%, and statistical differences can be detected (p=.000). While the "male politicians are more successful" statement is accepted at higher rates, at 49.7%, among male participants, statistically, there are huge differences between genders (p=.000). Conclusions: According to the research conducted, it is seen that traditional understanding weighs heavily, and the roles attributed to men and the perception of masculinity draw more attention. The fact that the research was conducted in a rural society where traditional understanding was dominant, substantially affected the results. The perspective of rural societies needs to change. Raising and increasing awareness on topics, such as gender roles, gender perception, and human rights with the health education method will be effective in changing the perceptions of men and women about one another.